2021
DOI: 10.4103/jcn.jcn_64_21
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hospital Readmissions

Abstract: Background: The neonatal period is important for establishing a strong healthy foundation and is also associated with high mortality and morbidity rates. This study aimed to determine the rate of neonatal hospital readmission and to identify the associations between the neonatal age at readmission and the length of stay (LOS) during readmission, the outcome of readmission, and the associated maternal and neonatal factors. Methods: A cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Previous research showed that males are more likely to be readmitted compared to females [9]. Our findings are consistent with this affirmation since there is a predominance of male newborns at readmissions (60.1%) and fewer females (39.8%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous research showed that males are more likely to be readmitted compared to females [9]. Our findings are consistent with this affirmation since there is a predominance of male newborns at readmissions (60.1%) and fewer females (39.8%).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, although the most prevalent diagnosis was infection, of bacterial or viral origin (bronchiolitis, enterocolitis, sepsis), the primary cause of readmission was represented by growth failure (25%). In a study conducted by Bawazeer M. et al the most common cause of readmission was respiratory disease, followed by jaundice, and fever [9]. Although only one patient was SARS-CoV-2 positive, fever was the most common COVID-19 patients admitted to a Pediatric Hospital in Bucharest [14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation